Multiple large shareholders, control contests, and implied cost of equity - Attig, Najah; Guedhami, Omrane; Mishra, Dev (Journal of Corporate Finance, 2008)
In this paper, we examine whether the presence of multiple large shareholders alleviates a firm's agency costs and information asymmetry manifested in the cost of equity financing. Using data for 1165 corporations from 8 East Asian and 13 Western European countries, we find evidence that the implied cost of equity decreases with the presence, number, and voting size of large shareholders beyond the controlling owner. We also find that the identity of the second largest shareholder is important in determining the risk of corporate expropriation in family-controlled firms. Our regional analysis reveals that, mainly in East Asian firms, multiple large shareholders structures exert an internal governance role in curbing private benefits and reducing information asymmetry, perhaps to sidestep deficiencies in the external institutional environment.